Progeny performance test results of Hungarian Simmental sires - Holló, Gabriella; Füller, Imre; Németh, Kristóf (Animal welfare, Ethology and Housing Systems (AWETH), 2023)
In this study, we analyzed the data of 1,571 bulls participating in progeny tests in a 20-year time interval, between 2002 and 2021. In the study, we analyzed only the effect of those sires who had more than 10 offsprings. It was created two groups based on the slaughter age and analyzed the 9 investigated traits, separately. At an older age slaughtered bull, weight gain is reduced, while live muscle score and post-slaughter EUROP muscle category score increase. The carcass meat yield also follows the previous trend, namely, the meat yield of progenies slaughtered at an older age is more favorable. The type classification effectively serves to improve the slaughtering traits, especially the muscularity through selection. Almost half of the bulls slaughtered at a younger age performed above average, which meant a significant surplus in sales. Based on the results, the meat production capacity of the sires exceeds that of the previous generations, so the male progenies can be further fattened to a higher final weight, without excessive accumulation of fat into their body. All these results definitely suggest to reconsider the fattening technology previously developed for the breed, namely the fattening to a higher final weight. To maintain and improve the role of the Hungarian Simmental breed in the slaughter cattle production, it is essential to apply modern breeding procedures –progeny test for meat production capacity – in everyday practice.